A Heuristic Evaluation for Deaf Web User Experience (HE4DWUX) - Yeratziotis, Alexandros; Zaphiris, Panayiotis (My University, 2018)
Websites that are usable and accessible can have a positive impact on the overall user experience. Usability Inspection Methods (UIMs) can be applied to evaluate and measure the usability. The current research in the fields of Web Accessibility and Human –Computer Interaction (HCI) is in need of additional UIMs that can be applied to also measure the accessibility, in addition to the usability alone. In this article, a novel UIM in the form of a heuristic evaluation is presented. The heuristic evaluation aims to support HCI experts and Web developers in designing and evaluating websites that provide positive user experiences to users who are deaf. This article discusses the development of the Heuristic Evaluation for Deaf Web User Experience (HE4DWUX). Following an iteration cycle, version 2 of the HE4DWUX is presented in Appendix A. An existing three-phase process to develop heuristics for specific application domains was applied to construct the HE4DWUX. The outcome of this research is 12 heuristics, with each containing its own set of checklist items to operationalize its applicability in measuring the Web user experience for users who are deaf. The heuristics and their checklist items can identify important aspects of design that will impact the Web user experience for this particular user group.
Keywords: Human computer interaction; Iterative methods; User interfaces; Websites; Deaf web user